Stent graft exclusion of a mycotic profunda femoris artery pseudoaneurysm with 2-year follow-up. Issue 6 (2nd June 2019) - Bakr, Ahmed Aboubakr-Esedik; Harding, James; Mahmood, Asif; Srinivasamurthy, Devaraj
Abstract : Mycotic pseudoaneurysms develop at sites of intimal disruption where bacterial invasion occurs. The conventional treatment involves arterial ligation, excision and debridement, followed by a bypass procedure at a later point. Recently, covered stent grafts have been used to treat mycotic arterial aneurysms either as temporary or definitive procedures. However, this is associated with a risk of stent graft infection, recurrence and rupture. There is a paucity of long-term results on the durability of such endovascular stent graft procedures in mycotic arterial pseudoaneurysms. We describe a successful endovascular covered stent repair of a mycotic profunda femoris artery pseudoaneurysm and follow-up of this repair at 2 years.